Fiscal reform and structural change in developing countries - Perry, Guillermo; McMohan, Gary; Whalley, John (London Macmillan, 2000)
Fiscal reforms and structural change in developing countries study the experience of countries involved in major tax reforms in the 1980s.The role of fiscal reform in stabilization and especially structural change can have on the fiscal deficit under diff
Keywords: Taxation-Developing countries; Fiscal policy-Developing countries